Green ECB Credit: One Step Too Far - Christian Pfister (Intereconomics, 2024)
Refinancing of green credit by the European Central Bank at favourable conditions has received the backing of some economists and policymakers. The article examines the motives put forward to support this proposal, as well as how it could be implemented and how its proponents try to ward off potential criticisms. A number of the issues raised by the proposal are then discussed from a logical, economic and a legal point of view. The article concludes that adopting the proposed measure would be going one step too far.
Keywords: E52; E58; Q54; Q58; 330; Central bank; Credit policy; Sustainable financing; EU countries; Zentralbank; Kreditpolitik; Nachhaltige Finanzierung; EU-Staaten